Risk Factors for Hepatic Encephalopathy in Hepatocellular Carcinoma After Sorafenib or Lenvatinib Treatment: A Real-World Study - Chen B; Zhang L; Cheng J; Wu T; Lei J; Yang X; Zhang R; Safadi R; Li Y; Si T; Lu Y (Dove Medical Press, 2022)
Bowen Chen,1,2,* Linzhi Zhang,2,3,* Jiamin Cheng,2,* Tong Wu,2 Jin Lei,2,4 Xu Yang,5 Rongling Zhang,6 Rifaat Safadi,7 Yinyin Li,2 Tongguo Si,3 Yinying Lu1,2,8,9 1Peking University 302 Clinical Medical School, Beijing, People's Republic of China; 2Senior Department of Hepatology, the 5th Medical Center of the PLA General Hospital, Beijing, People's Republic of China; 3Tianjin Medical University Cancer Institute and Hospital, Tianjin, People's Republic of China; 4Guizhou Medical University, Guiyang, People's Republic of China; 5Department of Liver Surgery, State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of China; 6Department of Infectious Disease, Beijing Ditan Hospital, Capital Medical University, Beijing, People's Republic of China; 7Liver Unit, Hadassah-Hebrew University Hospital, Jerusalem, Israel; 8Center for Synthetic & System Biology, Tsinghua University, Beijing, People's Republic of China; 9Guangdong Key Laboratory of Epigenetics, College of Life Sciences and Oceanography, Shenzhen University, Shenzhen, People's Republic of China*These authors contributed equally to this workCorrespondence: Yinying Lu, Peking University 302 Clinical Medical School, No. 100, Middle Road of the West 4th Ring, Beijing, 100039, People's Republic of China, Email luyinying1973@163.com Tongguo Si, Tianjin Medical University Cancer Institute and Hospital, Tiyuan North Huanhu West Road, Hexi District, Tianjin, 300060, People's Republic of China, Email sitg77@163.comPurpose: This study aimed to investigate the incidence rate and risk factors for hepatic encephalopathy (HE) among unresectable hepatocellular carcinoma (uHCC) patients with liver cirrhosis who received sorafenib or lenvatinib treatment.Patients and Methods: uHCC patients with cirrhosis who received first-line sorafenib or lenvatinib treatment between September 2014 and February 2021 were continually reviewed in our single-center retrospective study. The Hepatic Encephalopathy Scoring Algorithm was used to evaluate the occurrence and grade of HE during treatment, and logistic regression models were used to further explore the risk factors for HE.Results: A total of 454 eligible patients were enrolled in our study, with 214 and 240 patients in the sorafenib and lenvatinib groups, respectively. At time of data cut-off (2021- 12), the incidence of HE in sorafenib group (4.2%, 95% CI:2- 7%) was significantly lower than that in lenvatinib group (11.3%,95% CI:7- 15%) (p = 0.006), with alcoholic cirrhosis [OR: 5.857 (95% CI: 1.519- 22.591)], Child-Pugh > 7 [OR: 3.023 (95% CI: 1.135- 8.053)], blood ammonia ≥ 38.65 μmol/L [OR: 4.693 (95% CI: 1.782- 12.358)], total bile acid ≥ 29.5 μmol/L [OR: 11.047 (95% CI: 4.414- 27.650)] and duration of treatment ≥ 5.6 months [OR: 4.350 (95% CI: 1.701- 11.126)] to be risk factors for the occurrence of HE during first-line systemic therapy.Conclusion: In our study, for off-label uHCC patients (Child-Pugh > 7) with alcoholic cirrhosis, hyperammonemia, hypercholesterolemia, and estimated longer duration of treatment, the application of lenvatinib has to be cautious, which needs to be confirmed in future clinical trials.Keywords: hepatic encephalopathy, hepatocellular carcinoma, liver cirrhosis, sorafenib, lenvatinib